Raúl Prebisch and ECLAC in the institutionalization of Latin American social science - Scargiali, Enzo Andrés (2022)
The aim of this article is to analyse the transformations promoted by Raúl  Prebisch and ECLAC in the institutionalisation of Latin American social sciences. The questions that guide the research are: What were the main discussions that crossed the field of Latin American social science studies during the 1940s and 1950s? What was the place of Latin America in the institutionalization of the social sciences? First, it reconstructs the historical process of the institutionalisation of ECLAC and the different spaces of academic discussion in the formation of Raúl Prebisch. Then, it characterises the theoretical and political innovations brought about by Latin American structuralism in the framework of ECLAC during the 1950s. It also explores the criticisms of ECLAC's developmentalism by dependency theory during the 1960s. Finally, some considerations are made about the role of Raúl Prebisch in ECLAC.The methodological approach used is the historical sociology of Latin America. It is a discipline that rescues in a hybrid way the theories of socialchange, typical of sociology, and research supported by archives, from history. In addition, it has the potential to analyze sociohistorical processes with the prism of long, medium and short duration, allowing a long-termand procedural understanding.